Making, not breaking the young, aspiring athlete: the development of Prep to be PRO (Nærmere Best) – a Norwegian school-based educational programme - Roald Bahr; Grethe Myklebust; Christine Holm Moseid; Hege Heiestad (BMJ Open Sport & Exercise Medicine)
Background The most talented young athletes often face challenges related to sports health problems (ie, injury and illness), largely due to inappropriate training, condensed competition schedules and high demands. Previous preventive measures in Norway have lacked successful integration into young athletes’ routines, highlighting the need for a systematic approach to safeguarding their health.Objective To document the development of Prep to be PRO, an educational module-based programme, designed to support the development and protect the health of young athletes enrolled in sports junior high schools and sports academy high schools. Prep to be PRO aims to empower athletes with the relevant knowledge and skills to prevent health problems.Methods The development process, guided by the Translating Research into Injury Prevention Practice framework, involved extensive collaboration with school leaders, coaches and athletes. From June 2019 to June 2023, the process incorporated multidisciplinary input from more than 40 stakeholders, including health personnel, as well as experts in sports science, nutrition and sports psychology.Results Prep to be PRO consists of 10 modules tailored for both sports Junior high schools and sports academy high schools. The modules cover a range of topics, including performance training, growth and maturation, load progression, recovery, total load, nutrition and sports psychology. The programme is athlete-centred, but coach-driven, including student-active approaches, collaboration, use of digital tools and deep learning. Prep to be PRO is anchored in the National High School Curriculum, ensuring relevance and alignment with educational standards. Specific competence goals and learning objectives from the curriculum are addressed and linked to each individual module.Conclusions This educational programme appears to be a notable step forward in the Norwegian sports school’s approach. Specifically, it may enhance the focus on overall health, introduce an individualised approach and foster long-term athlete development. The integration into the national curriculum and the involvement of school staff in its delivery is expected to facilitate implementation. Future work will focus on the next phases of implementation, as systematic data collection from coaches and athletes, ongoing stakeholder engagement, continuous adaptation and support for educators to ensure fidelity and relevance. Updates and analyses from all evaluations will examine the programme’s effectiveness. Long-term sustainability will be secured by organisational commitment, resource alignment and integrating the initiative into existing structures.